PENGENDALIAN INTERNAL MELALUI RISK ASSESSMENT PENGADAAN BARANG DAN JASA PADA DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN KABUPATEN TOLITOLI - Maulana, Moh. Reza; Tinangon, Jantje J.; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to analyze the risk of procurement of goods and services at the Department of Public Housing and Residential Areas of Tolitoli Regency using model from ISO 31010, analyze the internal controls that need to be carried out based on COSO theory to minimize the risk of procurement of goods and services as well as mitigate any risks. This type of research is a qualitative research with a case study approach. Methods of data collection using interviews and documentation. Informants were selected using purposive sampling with the consideration of the most experienced and knowledgeable people about the research problem. The results show that there are 9 possible risks that occur in the process of procuring goods/services. Of the 9 risks, 3 risks are very high status, 4 risks are high status, 1 risk is moderate status and 1 risk is low status. Internal control has been carried out, but has not touched all aspects of internal control according to the internal control theory of COSO.Â